Relationship Marketing dan Customer Value Terhadap Customer Loyalty yang Dimediasi oleh Trust - Sulthoni Surya Saputra; Muzakar Isa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Relationship Marketing and Customer Value on Customer Loyalty mediated by Trust among Bank Jateng Sragen customers. Using a quantitative approach with a descriptive method, data were collected through a Likert-scale questionnaire. The Partial Least Square (PLS) analysis results indicate that Relationship Marketing and Customer Value have a positive and significant effect on Trust. However, Relationship Marketing does not significantly affect Customer Loyalty. Customer Value and Trust positively affect Customer Loyalty, with Trust mediating the relationship between Relationship Marketing and Customer Loyalty, as well as between Customer Value and Customer Loyalty. The limitations of this study include the focus only on the specified variables and the use of online questionnaires. Future research is recommended to add other variables and utilize interviews for more comprehensive data.